Pola Komunikasi Intrapersonal Orang Tua Dalam Membentuk Perilaku Anak - Fauziah Fauziah (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
Abstract Fauziah C1D112087, the supervisor I Dr.Muhammad. Zein Abdullah, M.Si and Mr. Abd Jaya S.Sos, M, Si as a mentor II. The problem in this research is How intrapersonal communication role of parents in shaping a child's behavior and behavior that is built on the relationship between parents communicate with their children. The purpose of this study to determine the role of intrapersonal communication the parents of children in shaping a child's behavior and to determine what behavior is generated by the child that was built on the relationship of parent and child. The benefits of this research is theoretically enriching khasana research mengaakat communicates concerns about the role of parents with children who are interesting study in science communication, especially communication intrapersonal. The location of this research carried out in Sub-WUA WUA Anawai districts kendari city. The theory used in this research is the theory of intrapersonal communication by Joseph D. Vito. Data obtained from this peneletian Deskripitif analyzed using qualitative techniques. The results of this study indicate that intrapersonal communication patterns of parents and children in Sub-WUA WUA Anawai districts kendari city was instrumental in shaping positive behavior from an early age to the child. Communication is always the parents can personally make a child's positive behavior, especially the behavior of independent, confident, and Openness. This independence is characterized by the inability of the child to do something themselves associated with everyday activities. Confident already can be demonstrated by the behavior of the child is capable of following the activities with its capabilities, and openness of the most prominent is characterized by the behavior of children who love to tell about their activities and what happened to his parents all day. Parents use their own ways to educate and care for their children. To be able to instill good character on the children themselves required effective intrapersonal communication patterns and a two-way means that the child understands what is desired by their parents and vice versa parents trying to understand their children to be good communication and as expected.